Passive Design Strategies for Energy Efficient Buildings in the Arabian Desert - Al-Tamimi, Nedhal (Frontiers in Built Environment, 2022)
This study aims to assess passive design features through the extensive modifications of building envelopes to affect the energy efficiency of residential buildings in hot arid climates. In support of the aim of this research, the annual electric energy bill of a typical residential building in Sharurah was collected and analyzed. Then, the DesignBuilder simulation program was used to investigate how different modifications of building envelopes could affect the energy consumption of the residential buildings under common scenarios. With this perspective, different types of glass, varied thermal insulation, green roof and shading devices were investigated. The simulation results show that thermal insulation can significantly reduce annual energy consumption by as high as 23.6%, followed by green roof, whereas shading devices and glazing system types were less superior. The results also indicate that the cost-effective combination of certain strategies can reduce total energy consumption by 35.4% relative to the base case of this research.